Facile Synthesis of Chiral Arylamines, Alkylamines and Amides by Enantioselective NiH‐Catalyzed Hydroamination. (24th September 2021) - Meng, Lingpu; Yang, Jingjie; Duan, Mei; Wang, You; Zhu, Shaolin
Abstract: Regio‐ and enantioselective hydroarylamination, hydroalkylamination and hydroamidation of styrenes have been developed by NiH catalysis with a simple bioxazoline ligand under mild conditions. A wide range of enantioenriched benzylic arylamines, alkylamines and amides can be easily accessed by nitroarenes, hydroxylamines and dioxazolones, respectively as amination reagents. The chiral induction in these reactions is proposed to proceed through an enantiodifferentiating syn ‐hydronickellation step. Abstract : Three types of enantioselective NiH‐catalyzed hydroaminations have been developed by using nitroarenes, hydroxylamines, or dioxazolones as aminating reagents. This modular process provides efficient access to a wide variety of enantioenriched α‐chiral benzylic arylamines, alkylamines, and amides from styrenes in high yields and with excellent enantioselectivities.